Incidence and cost of stress ulcer prophylaxis after discharge from the intensive care unit: A retrospective study - Tan, B.; Norman, R.; Litton, E.; Heath, C.; Hawkins, D.; Krishnamurthy, R.; Sonawane, R.; Anstey, Matthew (Australasian Academy of Critical Care Medicine, 2016)
Objective: To describe current patterns in initiation and cessation of proton pump inhibitors (PPIs) for stress ulcer prophylaxis (SUP) in intensive care units, and to assess the costs associated with inappropriate (non-evidence-based) SUP. Design, setting and participants: Retrospective observational study in five ICUs in Western Australia. We assessed the medical records of consecutive patients admitted to the ICUs between September 2013 and January 2015. Patients aged < 18 years were excluded. Results: We included 531 patients in the study. Of the 184 patients in whom PPIs were initiated for SUP in the ICU, 90 (48.9%) were still taking the therapy at the time of discharge from hospital. A documented indication for ongoing therapy was present in only nine patients (10%). We assumed a 10-year life expectancy after ICU discharge and that most patients continued taking a PPI, and calculated an additional cost of $180.20 per patient admitted to the ICU. This was based only on unnecessary PPI costs (ignoring costs of managing additional adverse events). The direct cumulative annual cost to the WA health system of PPIs continued unnecessarily for patients at discharge from hospital is estimated to be $250 800 for each year they continue to receive them. Conclusion: A substantial proportion of patients prescribed SUP in the ICU continue receiving this therapy at hospital discharge despite no clear indication. In addition to potential adverse clinical effects, this is associated with major direct and indirect cost implications.